Quality of work life and Innovative Culture at Kurdistan Universities - MUHAMMED, EMAN; D, NIHAT SALMA (The journal of contemporary issues in business and government, 2021)
Quality of work-life explains the well-being of induvial at their organizations. It is a very important factor in their balance between family and social life. In this respect, current paper aims to investigate the relations between quality of work-life, knowledge sharing, and innovative culture among university lecturers in Kurdistan Region of Iraq. To do this, 166 data have been collected from public and private universities in the region. Based on the results, it has been observed that work-life quality is significantly and positively related to the innovative culture at universities. Therefore, it is suggested that university administrators should provide a healthy work environment to their academic staff for the effectiveness of their departments.